Hoo-Doo Cowboys and Bronze Buckaroos : Conceptions of the African American West - Johnson, Michael K. (Michael Kyle), 1963- (Book collections on Project MUSE., 2014)
"Hoo-Doo Cowboys and Bronze Buckaroos undertakes an interdisciplinary exploration of the African American West through close readings of texts from a variety of media. This approach allows for both an in-depth analysis of individual texts and a discussion of material often left out or underrepresented in studies focused only on traditional literary material. The book engages heretofore unexamined writing by Rose Gordon, who wrote for local Montana newspapers rather than for a national audience; memoirs and letters of musicians, performers, and singers (such as W.C. Handy and Taylor Gordon), who lived in or wrote about touring the American West; the novels and films of Oscar Micheaux; black-cast westerns starring Herb Jeffries; largely unappreciated and unexamined episodes from the "golden age of western television" that feature African American actors; film and television westerns that use science fiction settings to imagine a "postracial" or "postsoul" frontier; Percival Everett's fiction addressing contemporary black western experience; and movies as recent as Quentin Tarantino's Django Unchained. Despite recent interest in the history of the African American West, we know very little about how the African American past in the West has been depicted in a full range of imaginative forms. Hoo-Doo Cowboys and Bronze Buckaroos advances our discovery of how the African American West has been experienced, imagined, portrayed, and performed"--